An assessment of the nutraceutical potential of Juglans regia L. leaf powder in diabetic rats. (September 2017) - Mollica, Adriano; Zengin, Gokhan; Locatelli, Marcello; Stefanucci, Azzurra; Macedonio, Giorgia; Bellagamba, Giuseppe; Onaolapo, Olakunle; Onaolapo, Adejoke; Azeez, Falilat; Ayileka, Adeola; Novellino, Ettore
Abstract: In this study, we evaluated the nutraceutical potential of Juglans regia L. (a dietary supplement and food-additive) by evaluating the in-vitro anti-diabetic potential and by assessing the in-vivo anti-hyperglycaemic, anti-hyperlipidaemic, and organ-protective effects of freshly-dried and powdered leaves of J. regia L. in diabetic rats. In the in-vivo experiments, dry powder of J. regia L. leaf (25, 50 and 100 mg/kg) was administered orally, twice daily (9.00 a.m. and 5 p.m.) to streptozocin-induced diabetic rats over a period of 28 days, during which body weight and blood glucose were monitored weekly. At the end of the experimental period, animals were sacrificed, blood was taken for assessment of lipid profile, antioxidant activity and liver/kidney biochemistry; while samples of the pancreas, liver and kidneys were fixed, processed, sectioned, and stained for general histology. Phytochemical evaluations of three extracts were carried out using HPLC-PDA validated procedures, while enzyme-inhibitory potentials were tested against α-amylase and α-glucosidase. In-vivo assays showed that twice-daily administration of J. regia L. leaf resulted in weight gain, glycaemic control, reversal of dyslipidaemia and biochemical evidences of liver/kidney injury, and protection against pancreas, liver and kidney tissue injury. Graphical abstract: